Kelompok Harapan Papua Baru: Meningkatkan Ekonomi Lokal melalui Inovasi Pengolahan Ikan - Asbudi Zamsan S (Universitas Cenderawasih, 2024)
This article examines the contribution of the Harapan Papua Baru Group, a community based business group in Merauke Regency, South Papua, engaged in fishery product processing since 2018. The primary focus of this study is to explore the group’s role in enhancing community welfare through innovative fish based products such as ALBUGRAN albumin oil, fish floss, fish balls, fish nuggets, and breaded shrimp. This research employs a qualitative method with a case study approach, involving in-depth interviews with group administrators, members, business partners, and local government representatives. The findings reveal that the group has successfully utilized local knowledge to add value to fishery products, supported by training, mentorship, and strong social solidarity. Their flagship product innovations have become an effective strategy for navigating market dynamics and improving competitiveness. However, significant challenges remain, such as product legality and production capacity limitations. Government and business partner support play a crucial role in the group's success. Moreover, the empowerment of women and the transformation of gender roles within the group contribute to improved family and community welfare. This article recommends strengthening collaboration between the government, community, and private sector to address existing challenges and sustain local resource-based economic empowerment programs. These findings enrich the literature on community empowerment through small-scale enterprises and sustainable fisheries resource management.This article examines the contribution of the Harapan Papua Baru Group, a community based business group in Merauke Regency, South Papua, engaged in fishery product processing since 2018. The primary focus of this study is to explore the group’s role in enhancing community welfare through innovative fish based products such as ALBUGRAN albumin oil, fish floss, fish balls, fish nuggets, and breaded shrimp. This research employs a qualitative method with a case study approach, involving in-depth interviews with group administrators, members, business partners, and local government representatives. The findings reveal that the group has successfully utilized local knowledge to add value to fishery products, supported by training, mentorship, and strong social solidarity. Their flagship product innovations have become an effective strategy for navigating market dynamics and improving competitiveness. However, significant challenges remain, such as product legality and production capacity limitations. Government and business partner support play a crucial role in the group's success. Moreover, the empowerment of women and the transformation of gender roles within the group contribute to improved family and community welfare. This article recommends strengthening collaboration between the government, community, and private sector to address existing challenges and sustain local resource-based economic empowerment programs. These findings enrich the literature on community empowerment through small-scale enterprises and sustainable fisheries resource management.